Configuration of integration features of genetic determination of erythrocyte antigen systems in patients with lichen planus of the oral mucosa - Kolenko, Юлія Геннадіївна; Zelinska, Наталія Антонівна; Tkach, Оксана Борисівна; Hryban, Олександр Михайлович (Actual Dentistry, 2023)
Aim: to study the genetic determination of erythrocyte blood antigens to the oral mucosa. Materials and methods. The subjects of the study were 248 LP patients aged 26–65 years. Determination of genetic markers in blood and saliva (oral fluid) was carried out using a hemagglutination reaction. Rabbit liquid absorbed sera anti-M, anti-N, goat liquid absorbed sera anti-P, goat liquid absorbed sera anti-Lea and anti-Leb, hemagglutinating iso-sera α, b and isoimmune anti-Rhesus sera anti-D group Oαb (I) were used Ab (II), Bα (III) and AB (IV) of the Kiev city blood transfusion station. Results. It was found that the largest number of patients had an erosive form of LLP without damage to the red border of the lips (36.5%) associated with gastric ulcer (34.7%).The established correlative relationship with antigens of the ABO (H) system in patients with LP with damage to the gastrointestinal tract indicates the comorbidity of these diseases. The risk groups for the erosive form of LP in patients with gastrointestinal pathology are detailed – (I)>A(II)>B(III) for the erosive form and A(II)>O(I)>B(III) for the hyperkeratotic form.“Critical” (P1, MN, Le(a-b+)) and “protective” (P1, N, MN, Le(a-b+)) phenotypes in patients with LP were determined. Conclusions. We believe that the established correlative relationship with erythrocyte antigens of the ABO(H) system in patients with LP with damage to the gastrointestinal tract indicates the comorbidity of these diseases with the subsequent need to take into account when planning preventive and therapeutic measures in this category of patients.